"Han i hennes ögon" - visuell representation av manliga kroppar i fotografier - Westerlundh,Michaela (2009)
This is a studie that analyzes a number of variants of the representations of masculinity and male bodies. The material is based on the exhibition “He in her eyes” by the artist Britt Marie Trensmar. The essay is to study the representation of masculinity expressed when women asked to shape their “image of man”. In the paper the images of male bodies in relation to the media representations of masculinity we usually face. Based on theories about bodies, gender, hegemonic and traditional masculinity construction, with the expression of the traditional masculinity norm where muscles and work are important characteristics, while it identifies a potential for an alternative understanding of male bodies and masculinity may mean for men and women by challenging gender norms.
Keywords: heterosexuella matrisen; ”Han i hennes ögon”; hegemonisk maskulinitet; visuell representation; motstånd; manliga kroppar